Mechanisms and Clinical Management of Ventricular Arrhythmias following Blunt Chest Trauma - Daniel H. Wolbrom; Aleef Rahman; Cory M. Tschabrunn (Cardiology Research and Practice)
Nonpenetrating, blunt chest trauma is a serious medical condition with varied clinical presentations and implications. This can be the result of a dense projectile during competitive and recreational sports but may also include other etiologies such as motor vehicle accidents or traumatic falls. In this setting, the manifestation of ventricular arrhythmias has been observed both acutely and chronically. This is based on two entirely separate mechanisms and etiologies requiring different treatments. Ventricular fibrillation can occur immediately after chest wall injury (commotio cordis) and requires rapid defibrillation. Monomorphic ventricular tachycardia can develop in the chronic stage due to underlying structural heart disease long after blunt chest injury. The associated arrhythmogenic tissue may be complex and provides the necessary substrate to form a reentrant VT circuit. Ventricular tachycardia in the absence of overt structural heart disease appears to be focal in nature with rapid termination during ablation. Regardless of the VT mechanism, patients with recurrent episodes, despite antiarrhythmic medication in the chronic stage following blunt chest injury, are likely to require ablation to achieve VT control. This review article will describe the mechanisms, pathophysiology, and treatment of ventricular arrhythmias that occur in both the acute and chronic stages following blunt chest trauma.